Synergistic Integration of MEMS and Spintronics for Precision Data Analytics in Cheminformatics - Bangshidhar Goswami (International Journal of Cheminformatics, 2024)
The transformational potential of merging spintronics and Micro-Electromechanical Systems (MEMS) technologies in cheminformatics is investigated in this work. Recent advancements in MEMS, particularly through the use of microbeam sensors and accelerometers, enhance the precision of data collection and processing, especially in biomedical applications such as drug delivery systems and chemical sensing. The synchronization of oscillations in MEMS devices leads to improved reliability and data accuracy, enabling the development of sophisticated cheminformatics models. Meanwhile, Spin-Torque Nano-Oscillators (STNOs) present a groundbreaking method for generating tunable microwave signals, which could significantly enhance signal processing capabilities in cheminformatics. Their low power consumption and compatibility with complementary metal-oxide-semiconductor (CMOS) technology make STNOs ideal for applications in molecular sensors and data logging systems. This paper elucidates the synergistic benefits of these technologies in facilitating real-time data transmission and analysis, ultimately advancing predictive modeling and chemical informatics databases.
Keywords: Cheminformatics; Spin-torque Nano-oscillators (STNOs); Spintronics; biomedical applications; data processing; micro-electromechanical systems (MEMS)